Efficacy of vitrectomy and epiretinal membrane peeling in eyes with dry age-related macular degeneration - Mason, John O (Clin Ophthalmol, 2015)
OBJECTIVE: To study the efficacy of epiretinal membrane (ERM) peeling in eyes with dry age-related macular degeneration (AMD). METHODS: We retrospectively analyzed patient charts on 17 eyes (16 patients) that underwent ERM peeling with a concurrent diagnosis of dry AMD. RESULTS: Eyes with concurrent dry AMD and with a good preoperative best-corrected visual acuity (BCVA) (better than or equal to 20/50) had a statistically significant mean BCVA improvement at 6 months after ERM peeling. There was a statistical increase in mean BCVA from 20/95 to 20/56 in dry AMD eyes, and no eyes showed worsening in BCVA at 6 months or at most recent follow-up. Five/seventeen (29.4%) eyes had cataract formation or progression. There were no other complications, reoperations, or reoccurrences. CONCLUSION: ERM peeling in eyes with dry AMD may show significant improvement, especially in eyes with good preoperative BCVA. The procedure is relatively safe with low complications and reoccurrences.